Power Generation by Resonant Self-Actuation - Joseph, Joel (Schriften des Instituts für Mikrostrukturtechnik am Karlsruher Institut für Technologie, 2023)
Research into micro energy harvesting systems has been driven by the need for self-sustaining, stable power sources for interconnected wireless sensors. Waste heat, particularly at temperatures below 200 °C, presents a promising but challenging energy source to recover using current conversion technology.